(untitled) (Altre Modernità, 2021)
For more than 30 years, the inner-German border as a physical border between the GDR and FRG no longer existed. From a linguistic perspective, unification can be assumed. The linguistic differences between the former East and West Germans are smaller than those between the different German dialect speakers. However, categories such as Ossi, East German or Wessi, West German can still be found today, although the terms for the inhabitants of the GDR (Ossi, Ostdeutsch, Ostler etc.) are more productive. The physical inner-German border seems to turn into a wall in people’s minds. This article takes up the current discourse and asks about the underlying patterns and frames that constitute this mental border or enable its reconstruction. Autobiographical narrative interviews with people of two age groups who grew up or were socialised at the former inner-German border serve as a basis.